THE PROBLEMS OF STUDENTS IN USING PAST TENSES - I Gusti Agung Vony Purnama (SPHOTA: Jurnal Linguistik dan Sastra, 2014)
ABSTRACT This study aims to find out the problem that was faced by the students including the type of errors that made by the students Year Intake 2013 Dual Degree Program STIKOM Bali in writing using English language. Besides that, this study aims to offer the Lesson Plan in writing based on the result of the analysis of this study. This study used the theory of English Grammar, and Error Analysis. The data of this study was from the students’ writing. There were 10 students as the sample in this study by using the collecting data method of quantitative method. There were 104 errors in active sentence of Simple Past tense as the findings of this study. This is the most error of the students. Then the error in using passive Simple Past was 8 errors. The last category of error was the error in using the Past Continues tense. It was found only 1 error for this category. Based on the Comparative Taxonomy, the source of the students’ error was the interference of their mother tongue or it is called as an Interlingual error. At last, the lesson plan was designed based on the result of the analysis of this study. It is expected to help the students in understanding the English writing to minimize the error. Keywords: Error Analysis, Linguistics Category Taxonomy, Lesson Plan